Sorting signals for PIN1 trafficking and localization. (2nd August 2016) - Marcote, María Jesús; Sancho-Andrés, Gloria; Soriano-Ortega, Esther; Aniento, Fernando
ABSTRACT: PIN-FORMED (PIN) family proteins direct polar auxin transport based on their asymmetric (polar) localization at the plasma membrane. In the case of PIN1, it mainly localizes to the basal (rootward) plasma membrane domain of stele cells in root meristems. Vesicular trafficking events, such as clathrin-dependent PIN1 endocytosis and polar recycling, are probably the main determinants for PIN1 polar localization. However, very little is known about the signals which may be involved in binding the μ-adaptin subunit of clathrin adaptor complexes (APs) for sorting of PIN1 within clathrin-coated vesicles, which can determine its trafficking and localization. We have performed a systematic mutagenesis analysis to investigate putative sorting motifs in the hydrophilic loop of PIN1. We have found that a non-canonical motif, based in a phenylalanine residue, through the binding of μA(μ2)- and μD(μ3)-adaptin, is important for PIN1 endocytosis and for PIN1 traffcking along the secretory pathway, respectively. In addition, tyrosine-based motifs, which also bind different μ-adaptins, could also contribute to PIN1 trafficking and localization.